The Great Polarization: Understanding to the Historical Shift Away from Social Action within Evangelicalism - Benjamin Elliott (Sekolah Tinggi Theologia Jaffray, 2021)
This paper aims to discuss the enduring shift of the evangelical church and the Christian and Missionary Alliance Church as a case study, away from active social action in the late nineteenth century and towards more hesitant involvement through the twentieth century and up to the present. Following Timothy Moberg, this paper recognizes a significant reversal of emphasis in evangelicalism during this season but argues that the root of this shift was not simply a change in focus but actually a great polarization of the ground of thought within the church. The paper involves a brief survey of some of the involved historical dynamics at play from Schleiermacher to Rauschenbusch but then concludes through a constructive comparison with the polarization of thought during the era of the Arian controversy to explore the possibility of hopeful pathways forward for the evangelical church in its dual mission to both preach God’s good news in Christ and to serve and care for the poor and vulnerable.